(untitled) (Journal of Surgical Sciences, 2019)
Background: Mislabeled specimens are one of the most common pre-analytic errors in a histopathology laboratory. As histopathology provides the final diagnosis for most of the diseases, labeling errors can lead to serious consequences leading to wrong treatments. Objectives: This study was carried out to find common pre-analytical errors of histopathology laboratory in the context of our country. Methods: Data were collected on six points of container labeling and nine points of requisition papers through simple check list over a period of one week. Results: Among 142 samples, labeling was found in 82.40% container. Among these labels, patients name, age, hospital registration number of the patients were absent in 19.01%, 26.06% and 90.85% samples respectively. Site of origin of the tissue in the container was absent in 71.83% samples. About 4.93% samples came to the laboratory without fixatives. Patients name, age, sex, site of origin of tissue, name of the referring physician and their contact numbers were found absent in 0.70%, 3.52%, 33.10%, 7.75%, 50% and 95.77% of requisition papers respectively. Clinical diagnosis was absent in 54.23% cases. A good proportion of container and requisition papers did not contain proper labeling, which is important not only for identification but also for histopathological diagnosis. Conclusion: We believe that, these errors occur due to lack of standard histopathology requisition form. Association of Surgeons and Pathologists can collaboratively form a standard requisition form for sending histopathology samples to different laboratories, which could easily reduce mislabeling errors in histopathology. Journal of Surgical Sciences (2013) Vol. 17 (2) :80-83